Geoglifos paracas de la costa sur: Cerro Lechuza y Cerro Pico - García Soto, Rubén (2013)
Traditionally, the manufacture of large found drawings on desert plains and hill slopes of the Peruvian south coast was at-tributed to the Nasca society. However, since the 1980s, it is known that this cultural manifestation is a tradition that wouldhave begun towards the 750 BC during the early part of the development of the Paracas culture. Paracas geoglyphs have beenreported from Pisco to the Rio Grande Basin of Nasca, particularly in the area of Palpa where the where they have identifiedmany of these geoglyphs. In this paper, we present groups of figures at Cerro Lechuza, Paracas, and Cerro Pico, Ica Valley, whichs how stylistic features of several phases of Paracas.